Social Impact and Self-Perception of Malocclusion among Adolescents in a Tertiary Centre of Eastern Nepal - Giri, Nidhi; Gautam, Ujwal (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Malocclusion, defined as an improper relationship between teeth in the opposite jaws, has been a prevalent disorder in recent decades. There has been an increased concern about dental appearance during childhood and early adulthood. Objective: To assess the social impact and self-perception of malocclusion among adolescents and to investigate whether the types and severity of malocclusion have any effect on adolescents’ social acceptance. Methods: A total of 301 participants were chosen from middle and high school with ages ranging from 12 to 19 years. After completion of the questionnaire to assess social impact, all the participants were examined using the Index of Orthodontic Treatment Need (IOTN). Results: Malocclusion severity has a negative correlation with satisfaction with dental appearance (σ: -0.385; p-value: <0.001). Similarly, the severity of malocclusion has weak positive correlation with treatment needs (σ: 0.156; p-value: 0.007) and social impact (σ: 0.171; p-value: 0.003). Conclusions: Different subjective domains of social impact and self-perception are influenced by the severity of malocclusion among adolescents visiting tertiary care center in Eastern Nepal.